TRANSPARENT TESTA GLABRA1 Regulates the Accumulation of Seed Storage Reserves in Arabidopsis . Issue 1 (7th July 2015) - Chen, Mingxun; Zhang, Bin; Li, Chengxiang; Kulaveerasingam, Harikrishna; Chew, Fook Tim; Yu, Hao
Abstract : An Arabidopsis transcription factor regulates the accumulation of seed storage reserves, including storage proteins and fatty acids. Abstract: Seed storage reserves mainly consist of starch, triacylglycerols, and storage proteins. They not only provide energy for seed germination and seedling establishment, but also supply essential dietary nutrients for human beings and animals. So far, the regulatory networks that govern the accumulation of seed storage reserves in plants are still largely unknown. Here, we show that TRANSPARENT TESTA GLABRA1 ( TTG1 ), which encodes a WD40 repeat transcription factor involved in many aspects of plant development, plays an important role in mediating the accumulation of seed storage reserves in Arabidopsis ( Arabidopsis thaliana ). The dry weight of ttg1-1 embryos significantly increases compared with that of wild-type embryos, which is accompanied by an increase in the contents of starch, total protein, and fatty acids in ttg1-1 seeds. FUSCA3 (FUS3), a master regulator of seed maturation, binds directly to the TTG1 genomic region and suppresses TTG1 expression in developing seeds. TTG1 negatively regulates the accumulation of seed storage proteins partially through transcriptional repression of 2S3, a gene encoding a 2S albumin precursor. TTG1 also indirectly suppresses the expression of genes involved in either seed development or synthesis/modification of fatty acids in developing seeds. In addition, we demonstrate that the maternal allele of the TTG1 gene suppresses the accumulation of storage proteins and fatty acids in seeds. Our results suggest that TTG1 is a direct target of FUS3 in the framework of the regulatory hierarchy controlling seed filling and regulates the accumulation of seed storage proteins and fatty acids during the seed maturation process.